Traduire en collectif le théâtre italien contemporain. Les enjeux politiques de La Langue du bourricot - Paolo Bellomo; Céline FRIGAU MANNING (Laboratoire Italien)
The theatre translation collective La Langue du bourricot (The donkey’s linguage) founded at Paris 8 University for current and former students from various disciplines, strives to propose a modus operandi, and a choice of contemporary dramaturgies and translations with marked political implications. This is what two of the collective’s founders explore here, by focusing on the first two plays translated by the group. Collaborative translation appears here as a dialectical space of listening and observing, which renounces individual possession and works slowly towards the transformation of the text into a collective voice. The Langue du bourricot is for its members both a point of departure and arrival: the gesture of translating itself, as much as the traductorial decisions and the choice of texts, seeks to found a political project.